Penerapan Aplikasi Wordwall sebagai Kuis Interaktif dalam Meningkatkan Minat Belajar Peserta Didik pada Mata Pelajaran PPKn di SMA Negeri 2 Tondano - Oktafiani, Windy; Tarigan, Yunika Anggreny Br (Tumoutou Social Science Journal, 2024)
The aim of this research is to find out how the application of the wordwall application as an interactive quiz can increase students' interest in learning in Civics subjects at SMA Negeri 2 Tondano. The method used in this research is qualitative research. The technique used in data collection is direct observation in class. The problem at SMA Negeri 2 Tondano is students' declining interest in learning in Civics subjects. The results of this research are that the application of the wordwall application as an interactive quiz in the teaching and learning process can create a learning atmosphere that attracts students' attention and fosters students' enthusiasm for learning so that it can increase students' interest in learning and the material delivered by the teacher is easy for students to understand well. and the learning process can run effectively. Researchers hope that this research can become a reference to arouse students' interest in learning in the teaching and learning process by implementing the wordwall application as an interactive quiz.